Data mart for decision support system: a case study at Petron Fuel International Sdn Bhd / Norzareena Zahari - Zahari, Norzareena (2015)
In organisation, manager plays an important function in decision making. As the volume of data evolved and the methods of analyzing have improved, therefore organisation have been integrating data more firmly into decision making process. Manager need to know about the sales person performance and how to gain rapid insight into fast-growth products, and services. Therefore a Decision Support System (DSS) play important roles for manager as a decision maker in organisation. To answer question that arise from user information needs, a data mart was create to distill the relevant information to targeted DSS users. This project presents the design of data mart for sales analysis using dimensional modeling techniques. The designed data mart was implemented from current tools in Commercial Vehicle Sales (CVS). Appropriate data mart dimensions and fact were modeled in order to ease data analysis and queries. Data models based on dimensional modeling (snowflakes) are provided and discussed. This project also intended to design and develop data mart in order to assists in decision making process. One of the most use DSS interface in organisation are Microsoft's Excel. Microsoft Excel do provides the ability to generate a output like examples pie chart, bar charts and many more function. The capability of Mircosoft Excel as a DSS for organisation is become slower as the data getting growth over a time. This results to an error for the some of the require output and automatically affected in decision making process. Throughout an analysis of current tools that being used by the manager in Commercial Vehicles Sales team (CVS) of Petron Fuel International, found out that Microsoft Excel as DSS interface was produce a non-accuracy on the monthly basis reports. Through this project, the problems from current tools for CVS have been pointed out and the recommendations have been analysed based on the development design review.